Tunable spacing of O-band Multiwavelength Brillouin fiber laser - Norizan, Siti Fatimah; Zulkifli, Mohd Zamani (Institute of Electrical and Electronics Engineers, Inc., 2016)
A tuneable spacing of O-band multiwavelength Brillouin fiber laser is demonstrated. The channel spacing is varied by employing two types of cavities. A full closed linear cavity produce multiwavelength Brillouin fiber laser with 12.5GHz meanwhile a ring cavity provide channel spacing of 25.0 GHz. By combining these two cavities and employing optical channel switch the channel spacing are varied. The comparison of Brillouin threshold between O-band and C-band demonstrated. An O-band transmission window is used instead of C-band due to its lower Brillouin threshold.